Pengaruh Variasi Waktu Pemeraman Terhadap Daya Dukung Tanah Lempung dan Lanau yang Distabilisasi Menggunakan Semen pada Kondisi Tanpa Rendaman (Unsoaked) - Pandiangan, Bravo; Iswan, Iswan; Jafri, Muhammad (Universitas Lampung, 2016)
Soil is the material that serves as a support for the construction base. Each region has different soil characteristics in other areas, there has a carrying capacity of good to bad or poor. Clay and silt soil has a bearing capacity and low soil properties. To overcome this, the need to improve the soil natures with the stabilization method. Stabilization is to improve the physical and mechanical properties of the soil so that it meets certain technical requirements. One way is with a cement stabilization. In this study, the cement used is a cement-type portland cement. This study aimed to compare the value of CBR clay and silt before and after stabilized by the addition of cement. Soil used is a type of clay taken from the village of Rawa Sragi, District Jabung, East Lampung district and silt types from Yosomulyo Village, East Metro District, Metro City. In the modified proctor compaction test results, the addition of cement on clay and silt proven to increase the value of the maximum volume weight (γd) continuously. While the value of the optimum water content (ωopt) a decline that is not too significant on at every level of the cement. For a density value of clay and silt mixed cement has increased compared with the original soil density. In testing the CBR without soaking in a mixture of cement with modified proctor compaction CBR values obtained optimum cement content of 9% and ripening 28 days amounted to 107.6% in clay, silt soil while the CBR value without immersion saw the largest increase in cement content 9% and ripening 28 days 58%. The addition of portland cement is proven to increase the value of CBR significantly compared with the both real soil Keywords: Cement, Clay, Silt, CBR, Soil Bearing Capacity